2008
DOI: 10.1007/bf03175542
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial fermentation induced mineral dynamics during the production of Mbuja fromHibiscus sabdariffa seeds in earthen-ware pots

Abstract: In the northern parts of Cameroon, Hibiscus sabdariffa seeds are traditionally fermented in earthen-ware pots to produce a condiment known as Mbuja. This study was carried out to access the effect of fermentation on the mineral content of Hibiscus sabdariffa seeds during the process of fermentation. The bacterial species associated with this process of fermentation were screened, numbered and identified at the beginning and at the end of the process. Similarly, the mineral content of grains was determined at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Domestic water pots for potable water usage are the most common example of this (Trivedi et al, 2017). Beverages fermented in earthen pots are more intoxicating and of higher yield and earthen wears put a positive effect on minerals content (Roy et al, 2012;Mohamadou et al, 2008). Traditional preparation of Mbujha in earthenware pots by fermenting Hibiscus sabdariffa seeds significantly increases the aluminium, manganese, magnesium, sodium, zinc and decreases the calcium level (Mohamadou et al, 2008).…”
Section: Earthenmentioning
confidence: 99%
See 1 more Smart Citation
“…Domestic water pots for potable water usage are the most common example of this (Trivedi et al, 2017). Beverages fermented in earthen pots are more intoxicating and of higher yield and earthen wears put a positive effect on minerals content (Roy et al, 2012;Mohamadou et al, 2008). Traditional preparation of Mbujha in earthenware pots by fermenting Hibiscus sabdariffa seeds significantly increases the aluminium, manganese, magnesium, sodium, zinc and decreases the calcium level (Mohamadou et al, 2008).…”
Section: Earthenmentioning
confidence: 99%
“…Beverages fermented in earthen pots are more intoxicating and of higher yield and earthen wears put a positive effect on minerals content (Roy et al, 2012;Mohamadou et al, 2008). Traditional preparation of Mbujha in earthenware pots by fermenting Hibiscus sabdariffa seeds significantly increases the aluminium, manganese, magnesium, sodium, zinc and decreases the calcium level (Mohamadou et al, 2008). It is observed that boiling of water in earthen pots decreases the heavy metal concentration in water due to soil composition (Kandavel et al, 2015).…”
Section: Earthenmentioning
confidence: 99%
“…Food quality is generally influenced by the processing techniques used. It was found to be largely influenced by a variety of factors and micro-organisms (Mohamadou et al, 2008). Since old time, various methods have been used to process and to preserve foods.…”
Section: Introductionmentioning
confidence: 99%